(untitled) (Indian Journal of Animal Production and Management, 2026)
The majority of the Indian economy is in the hands of small and marginal farmers, with 80% of total land holdings having less than 1 ha of cultivable land. Integration of livestock with crops provides scope for effective utilization of byproducts, which assures the profitability of the farming system. An Integrated Farming System approach is required to enhance the living standards of small and marginal farmers. The present study revealed the profitable farming systems in major farming situations and their diversification. It was observed that the farming system consisting of seasonal crops along with dairy, sheep, and poultry was found to be more profitable than the cultivation of crops alone. The economic sustainability of the farming systems was evaluated through the Sustainability Value Index (SVI). Most of the farming systems in the rainfed black soils were found to be sustainable. However, only one farming system in rainfed red soils was found to be sustainable.The Simpson Index of Diversification (SID) was also assessed, and more diversification was observed in the farming systems under rainfed red soils. The results of the study are useful for small and marginal farmers to adopt suitable farming systems.